The Daily Grind: The Rotary Quern and Nova Scotia’s Scots - Stanley-Blackwell, Laurie (Material Culture Review, 2015)
Although the history of the quern (hand mill) in Scotland has attracted extensive academic attention, the cultural diffusion of this domestic tool to North America is little known. This preliminary investigation into quern use among Nova Scotia’s Scottish immigrants reveals that querns, despite their cumbersome size and weight, were transported to the colony and were regarded as tangible and portable symbols of a distinctive way of life. The quern’s utility and intrinsic value were augmented by its link to story and song, as well as cultural self-reliance, male physical strength, and female participation in rural food production. This study points to the need for a quern inventory in Nova Scotia to establish a more comprehensive profile of the distribution, design, and lithology of querns used by the early Scottish settlers..